Windows on the mind - "Harth, Erich" (Middlesex, 1985)
Discusses how experimental achievements have increased understanding of the workings of the brain and mind, explaining the complex correlation between brain, mind, and consciousness and detailing evidence of the physical basis for consciousness
Keywords: Knowledge